Noncyclic Geometric Quantum Gates with Smooth Paths via Invariant‐Based Shortcuts. Issue 6 (29th April 2021) - Ji, Li‐Na; Ding, Cheng‐Yun; Chen, Tao; Xue, Zheng‐Yuan
Abstract: Nonadiabatic geometric quantum computation is dedicated to the realization of high‐fidelity and robust quantum gates, which are necessary for fault‐tolerant quantum computation. However, it is limited by cyclic and mutative evolution path, which usually requires longer gate‐time and abrupt pulse control, weakening the gate performance. Here, a scheme to realize geometric quantum gates with noncyclic and nonadiabatic evolution via invariant‐based shortcuts is proposed, where universal quantum gates can be induced in one step without path mutation and the gate time is also effectively shortened. Our numerical simulations show that, comparing with the conventional dynamical gates, the constructed geometric gates have stronger resistance not only to systematic errors, induced by both qubit‐frequency drift and the deviation of the amplitude of the driving fields, but also to environment‐induced decoherence effect. In addition, this scheme can also be implemented on a superconducting circuit platform, with the fidelities of single‐qubit and two‐qubit gates higher than 99.97% and 99.84%, respectively. Therefore, this scheme provides a promising way to realize high‐fidelity fault‐tolerant quantum gates for scalable quantum computation. Abstract : Noncyclic geometric quantum computation with smooth paths and its superconducting circuit implementation are proposed with smooth evolution trajectories, where the gate‐time is also effectively shortened. Numerical simulation shows that the constructed quantum gates have stronger resistance to both systematic errors and environment‐induced decoherence. Therefore, this scheme provides a promising alternative toward scalable and fault‐tolerant quantum computation.